DEVELOPING STUDENTS’ READING SKILL THROUGH AUTHENTIC MATERIALS - Abdullaeva Gulkhayo Ulugbekovna (Web of Journals Publishing, 2024)
In modern language classrooms, authentic materials have already been an integral part of language learning process due to the opportunities they provide for classroom interaction among FLLs (Foreign language learners) and SLSs (Second language learners). When applied appropriately, authentic texts can be of great benefit to language learners and teachers in general. For this reason, this article will explore the benefits and challenges of using authentic materials to teach English language, in particular, reading skills.
Keywords: Authentic materials, reading skill, texts, suitability, exploitability, readability, challenges.